Observation and branching fraction measurement of the decay Ξ−b → Λ0bπ - Bachmann, Sebastian; Borsato, Martino; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review, 2023)
The decay Ξ−𝑏→Λ0𝑏⁢𝜋− is observed using a proton-proton collision data sample collected at center-of-mass energy √𝑠=13 TeV with the LHCb detector, corresponding to an integrated luminosity of 5.5 fb−1. This process is mediated by the 𝑠→𝑢⁢¯𝑢⁢𝑑 quark-level transition, where the 𝑏 quark in the Ξ−𝑏 baryon is a spectator in the decay. Averaging the results obtained using the two Λ0𝑏 decay modes, Λ0𝑏→Λ+𝑐⁢𝜋− and Λ0𝑏→Λ+𝑐⁢𝜋−⁢𝜋+⁢𝜋−, the relative production ratio is measured to be (𝑓Ξ−𝑏/𝑓Λ0𝑏)⁢ℬ⁡(Ξ−𝑏→Λ0𝑏⁢𝜋−)=(7.3±0.8±0.6)×10−4. Here the uncertainties are statistical and systematic, respectively, and 𝑓Ξ−𝑏⁡(𝑓Λ0𝑏) is the fragmentation fraction for a 𝑏 quark into a Ξ−𝑏 (Λ0𝑏) baryon. Using an independent measurement of 𝑓Ξ−𝑏/𝑓Λ0𝑏, the branching fraction ℬ⁡(Ξ−𝑏→Λ0𝑏⁢𝜋−)=(0.89±0.10±0.07±0.29)% is obtained, where the last uncertainty is due to the assumed SU(3) flavor symmetry in the determination of 𝑓Ξ−𝑏/𝑓Λ0𝑏.
Im Titel ist b tiefgestellt, die 0 hochgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, L. Carus, R. Caspary, C. Cocha Toapaxi, M. De Cian, G. Frau, F. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, R. Skuza, P.R. Pais, G. Tuci, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1079 weitere]
Gesehen am 25.06.2024